Baltic Peoples in Kazakhstan: Culture, History of Settlement and Contribution to the Economy of Kazakhstan - Mazhitova, Zhanna; Saktaganova, Zauresh; Utegenov, Marat; Balykova, Akkaiyn; Kozina, Valeria; Yeleukhanova, Svetlana (Journal of Ecohumanism, 2024)
In the article, the authors provide an analysis of some issues of Baltic everyday life: the history of its appearance on the territory of Kazakhstan, everyday work in the virgin lands and family and religious life. The sources for archival, statistical and ego-documents (personal archives, interviews and recollections of the participants of the events). The state and party organs imperatively implemented the standards of contribution and ‘behaviour’ of the Soviet republics in the implementation of the virgin project, shaping various positive/negative socio-cultural everyday practices. According to the authors, the Soviet leadership created ‘deviations’ in the form of protest sentiments, inter-ethnic conflicts and discontent of national minorities on a wide range of political and socio-economic issues through ideological principles.